2021
DOI: 10.3390/e23050503
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Variational Mode Decomposition and Permutation Entropy with Their Application in Feature Extraction of Ship-Radiated Noise

Abstract: The complex and changeable marine environment surrounded by a variety of noise, including sounds of marine animals, industrial noise, traffic noise and the noise formed by molecular movement, not only interferes with the normal life of residents near the port, but also exerts a significant influence on feature extraction of ship-radiated noise (S-RN). In this paper, a novel feature extraction technique for S-RN signals based on optimized variational mode decomposition (OVMD), permutation entropy (PE), and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…It is concluded that WPE not only has the same advantages as PE, but also can detect the complexity of dynamic mutation by quantifying amplitude information. Concurrently, other application fields of PE and WPE have also received great attention [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that WPE not only has the same advantages as PE, but also can detect the complexity of dynamic mutation by quantifying amplitude information. Concurrently, other application fields of PE and WPE have also received great attention [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The probability distribution of ordinal patterns (OP) implicitly captures information about the temporal structure of the time series and thus allows the extraction of several promising ordinal pattern-based indicators. These indicators are useful in a growing number of applications including biomedical signal and image processing [ 6 , 10 , 11 , 15 , 31 , 33 , 38 ], fault bearing diagnosis [ 30 , 39 , 40 , 41 , 42 , 43 , 44 ], financial time series analysis [ 7 ] and engineering physics [ 18 , 35 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the PE has the ability to capture hidden dynamics of time series, various extensions of the PE, called multiscale PE (MPE), have been proposed to explore in depth the internal structure of signals at different time scales. Among the MPE techniques, we cite coarse-graining MPE [ 53 ], composite MPE [ 54 ], refined composite MPE [ 12 ], downspamling PE (DPE) [ 55 ], composite DPE [ 31 ], refined composite DPE [ 31 ], hierarchical PE [ 56 ], and data-driven decomposition-based MPE [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 57 , 58 , 59 ]. The main idea of these PE-based techniques is to combine PE with a preprocessing step of the signal of interest in order to reduce the number of patterns related to noise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2002, PE was proposed for the first time; its advantages are simplicity, exceedingly fast calculation, robustness, etc. [ 25 , 26 , 27 ]. With the development of PE, it has gradually become more widely used in the field of SNS feature extraction, and the improved algorithms of PE were proposed and applied successively in the following years, such as reverse permutation entropy (RPE) [ 28 ], weighted-permutation entropy (W-PE) [ 29 , 30 ], and multi-scale permutation entropy (MPE) [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%